О построении целевой функции производственной системы - Пигнастый, О.М. (Видавничий дім "Академперіодика" НАН України, 2007)
The goal function of a manufacturing system with mass production output is constructed with the use of the variational principle. The equations for the central manufacturing trajectory are defined. Euler's equations for the central base product of the manufacturing system are given.